BRAC University new campus development project construction schedule (April, 2021- June, 2021) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding BRAC University new campus development project construction schedule (April, 2021- June, 2021).